2014
DOI: 10.1111/ina.12163
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particles from electric appliances and cooking pans: experiments suggesting desorption/nucleation of sorbed organics as the primary source

Abstract: Ultrafine particles are observed when metal surfaces, such as heating elements in electric appliances, or even empty cooking pans, are heated. The source of the particles has not been identified. We present evidence that particles >10 nm are not emitted directly from the heating elements or the metal surfaces. Using repeated heating of an electric burner, several types of cooking pans, and a steam iron, the increase in the number of particles (>10 nm) can be reduced to 0. After the devices are exposed to indoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 40 publications
5
59
1
Order By: Relevance
“…This result is consistent with experiments reported by Wallace et al. (), which showed that heated metal surfaces (e.g., empty cooking pans) can produce high UFP emissions with no measurable FP emissions, while frying meat is associated with high FP emissions (Abdullahi et al., ; Dacunto et al., ; Zhang et al., ). The UFP and FP means in most restaurants varied widely, and the correlation between the UFP and FP restaurant means measured on the 73 visits was not statistically significant (Figure S2 in Data S1).…”
Section: Resultssupporting
confidence: 91%
“…This result is consistent with experiments reported by Wallace et al. (), which showed that heated metal surfaces (e.g., empty cooking pans) can produce high UFP emissions with no measurable FP emissions, while frying meat is associated with high FP emissions (Abdullahi et al., ; Dacunto et al., ; Zhang et al., ). The UFP and FP means in most restaurants varied widely, and the correlation between the UFP and FP restaurant means measured on the 73 visits was not statistically significant (Figure S2 in Data S1).…”
Section: Resultssupporting
confidence: 91%
“…We note that Asian‐style cooking could generate much higher particulate emissions than Western‐style cooking (100 mg kg −1 ); therefore, our results cannot be generalized to other locations. We also note that we have not observed particle emissions from heated empty pans due to desorption/nucleation of sorbed organics recently suggested as a primary source of particles from cooking processes . Therefore, we have not considered this additional source in our model, although such processes can still occur if pans are not cleaned well.…”
Section: Resultsmentioning
confidence: 95%
“…Cooking‐induced primary and secondary pollution is not only controlled by the cooked ingredients and cooking style or setting (fuel, pan, oil used, and cooking method), but also depends on the air exchange rates (eg, induced by ventilation) and the oxidant precursor levels indoor and outdoor . Even though, several models describing indoor air pollution from different sources exist, none of these addresses both the particle and gas‐phase emissions from cooking, where the aforementioned parameters driving the pollutants emission, their transformation, and their losses can be systematically varied.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may result from the cleaning, pre-conditioning, and more repeat experiments in the earlier study. This observation derives from the hypothesis that the particles were formed by volatilization of organics compounds that were deposited on cooktop, oven or broiler burner surfaces, as reported by (Wallace et al, 2015) for electric burners and other hot surfaces.…”
mentioning
confidence: 87%